Effect of corporal suspension and pendulum exercises on neuromuscular properties and functionality in patients with medullar thoracic injury. (March 2019) - Frison, Verônica B.; Lanferdini, Fábio Juner; Geremia, Jeam Marcel; de Oliveira, Charlene B.; Radaelli, Régis; Netto, Carlos Alexandre; Franco, Alexandre R.; Vaz, Marco Aurélio
Abstract: Background: Traumatic spinal cord injury (TSCI) is one of the most devastating injuries that has a physical impact on patients. The CHORDATA® method involves suspension and pendulous exercises and has been clinically used to treat patients with TSCI. Although empirically used to treat neurological patients, there is no scientific evidence of the efficacy of this method. Purpose: To evaluate the chronic effects of CHORDATA® method on torque, muscle activation, muscle thickness, and functionality in patients with traumatic spinal cord injury. Methods: Twenty-six male patients with medullar thoracic injury were randomly categorised into two groups: intervention group (n = 14) and control group (n = 12). Rehabilitation program comprised of 16 sessions of body suspension and pendulum exercises (twice/week). The maximal voluntary isometric trunk flexion and extension torques, muscle activation and thickness (external and internal oblique, rectus and transversus abdominis, longissimus, and multifidus muscles), and functionality (adapted reach test) were evaluated before and after of rehabilitation program. Findings: A significant increase was observed in maximal voluntary isometric torque (flexion, 58%; extension, 76%), muscle activation of the rectus abdominis muscle, and muscle thickness of all intervention group muscles, without changes in the control group. Compared to the pre-intervention period, the intervention group also showed improvement in functionality at post-intervention, but no such differences were noted in the control group. Interpretation: The corporal suspension and pendulum exercises training improved rectus abdominis muscle activation, trunk muscles structure and strength, and reaching capacity in medullar thoracic injury patients. Highlights: Traumatic spinal cord injury has physical and psychological impacts on patients A rehabilitation strategy involving suspension and pendulous exercises is proposed Exercises led to increased isometric torque, muscle activation and muscle thickness Intervention group also showed improvement in functionality at post-intervention The corporal suspension and pendulum exercises training program was effective